The effects of host immunity on virulence-transmissibility relationships in the rodent malaria parasite Plasmodium chabaudi. - Mackinnon, M; Read, A (2003)
Here we examined the impact of host immunity on relationships between parasite virulence, transmission rate, intrinsic growth rate and host recovery rate in the rodent malaria parasite, Plasmodium chabaudi. Groups of naïve and immunized mice were infected with 1 of 10 cloned lines of parasites and their infection dynamics were monitored for 19 days. We found that (1) host immunity reduced the growth rate, virulence, transmission rate and infection length, with a consequent 3-fold reduction in life-time transmission potential, (2) clone means for these traits ranked similarly across naïve and immunized mice, (3) regression slopes of transmission potential on growth rate, virulence and infection length were similar in naive and immunized mice, (4) virulence and infection length were positively correlated in immunized but not naïve mice, and (5) for a similar level of parasite growth rate and virulence, transmission potential and infection length were lower in immunized than naïve mice. Thus host immunity reduced all these fitness traits in a manner consistent with direct parasite-driven biological links among them. These results support the basic assumption underlying our theory that predicts that anti-disease vaccines will select for higher virulence in those microparasites for which virulence is integrally linked to transmission.